(untitled) (Legal journal - Research in Legal and Social Sciences, 2023)
The purpose of this paper is to address in a practical spirit an issue that is often unknown, as well as useful for legal operators, and for the Spanish investor, regarding its role in the process of incorporation of the stock corporation in the Paraguayan legal system and its comparison with the Spanish one. For this purpose, it was necessary to analyze the Paraguayan legal system from its roots and current, serving as a common thread between operators, the result of historical characteristics closely linked to the Spanish, considering that there is currently a significant presence of Spaniards in the Paraguayan investment market. It is also intended to shed light on the existing regulatory differences in this area. For this reason, the method used in the research is qualitative, descriptive and non-experimental, and documentary analysis was used as a data collection technique. The theoretical sample is made up of the civil and commercial legislations of both States that constitute the basis for the development of this work, which shows the differences and similarities between both legislations.